2017
DOI: 10.1080/15384101.2017.1317409
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent regulation of rDNA condensation inSaccharomyces cerevisiae

Abstract: Chromatin condensation during mitosis produces detangled and discrete DNA entities required for high fidelity sister chromatid segregation during mitosis and positions DNA away from the cleavage furrow during cytokinesis. Regional condensation during G1 also establishes a nuclear architecture through which gene transcription is regulated but remains plastic so that cells can respond to changes in nutrient levels, temperature and signaling molecules. To date, however, the potential impact of this plasticity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 67 publications
(59 reference statements)
5
52
0
Order By: Relevance
“…Cell cycle progression from log phase into mitosis was confirmed by flow cytometry (Figure 1A). As expected, mitotic wildtype cells maintained at 23°C contained long rDNA loops while the rDNA of mitotic cells shifted to 37°C during the final hour of incubation hypercondensed into very short loops (Figure 1B), consistent with prior findings (Shen and Skibbens, 2017a; Matos-Perdomo and Machín, 2018a). Prior analyses of these cells revealed that only a fraction of scc2-4 mutant cells contain condensed rDNA loci at 23°C, a level which is retained after shifting to 37°C during the final hour of incubation (Shen and Skibbens, 2017b).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Cell cycle progression from log phase into mitosis was confirmed by flow cytometry (Figure 1A). As expected, mitotic wildtype cells maintained at 23°C contained long rDNA loops while the rDNA of mitotic cells shifted to 37°C during the final hour of incubation hypercondensed into very short loops (Figure 1B), consistent with prior findings (Shen and Skibbens, 2017a; Matos-Perdomo and Machín, 2018a). Prior analyses of these cells revealed that only a fraction of scc2-4 mutant cells contain condensed rDNA loci at 23°C, a level which is retained after shifting to 37°C during the final hour of incubation (Shen and Skibbens, 2017b).…”
Section: Resultssupporting
confidence: 90%
“…Cohesins play a critical role in chromosome condensation, including across the rDNA locus, such that mutation in either cohesin subunits (Mcd1/Scc1, Pds5 or Scc3) or regulators (Eco1 or Scc2) all result in severe rDNA condensation defects (Guacci et al, 1997; D’Ambrosio et al, 2008; Tong and Skibbens, 2015; Skibbens et al, 1999; Hartman et al, 2000; Woodman et al, 2015; Orgil et al, 2015). These observations formally suggest that de novo cohesin deposition during mitosis may play a critical role in hyperthermic-induced rDNA hypercondensation, in contrast to the decondensation of rDNA into ‘puffs’ that occurs upon either cohesin inactivation or dissociation (Guacci et al, 1997; Ciosk et al, 2000; Shen and Skibbens, 2017a). Here, we test whether de novo cohesin deposition promotes hyperthermic-induced rDNA hypercondensation by inactivating the Scc2,4 heterocomplex that is required for cohesin deposition onto DNA (Ciosk et al, 2000; Watrin et al, 2006).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations